THE DYNAMICS OF INDUSTRIAL DEVELOPMENT OF THE USSR IN 1960-70- IES - Yuliya A. Davidova; Vladimir V. Gromenko (Статистика и экономика, 2016)
The article analyzes the main directions of development of the industry of the USSR in 1960-70-sthe Authors thoroughly and consistently consider the dynamics of industrial growth in the consideredyears, reforms in the sphere of industry, payingattention to their advantages and disadvantages.The study is the analysis of statistical sources 70s,materials economic discussion 1962. The Authors concluded that the reduction in the pace of industrialdevelopment is primarily connected with the factthat the model of socialist economy has exhaustedits resources.